Collateral blood flow measurement with intravoxel incoherent motion perfusion imaging in hyperacute brain stroke. (21st May 2019) - Federau, Christian; Wintermark, Max; Christensen, Soren; Mlynash, Michael; Marcellus, David G.; Zhu, Guangming; Martin, Blake W.; Lansberg, Maarten G.; Albers, Gregory W.; Heit, Jeremy J.
Abstract : Objective: To determine if intravoxel incoherent motion (IVIM) magnetic resonance perfusion can measure the quality of the collateral blood flow in the penumbra in hyperacute stroke. Methods: A 6 b values IVIM MRI sequence was acquired in stroke patients with large vessel occlusion imaged <16 hours of last seen well. IVIM perfusion measures were evaluated in regions of interest drawn in the infarct core (D < 600 mm 2 /s), in the corresponding region in the contralateral hemisphere, and in the dynamic susceptibility contrast penumbra. In patients with a penumbra >15 mL, images were reviewed for the presence of a penumbra perfusion lesion on the IVIM f map, which was correlated with infarct size metrics. Statistical significance was tested using Student t test, Mann-Whitney U test, and Fisher exact test. Results: A total of 34 patients were included. In the stroke core, IVIM f was significantly lower (4.6 ± 3.3%) compared to the healthy contralateral region (6.3 ± 2.2%, p < 0.001). In the 25 patients with a penumbra >15 mL, 9 patients had an IVIM penumbra perfusion lesion (56 ± 76 mL), and 16 did not. Patients with an IVIM penumbra perfusion lesion had a larger infarct core (82 ± 84 mL) at baseline, a larger infarct growth (68 ± 40 mL), and a larger final infarct size (126 ± 81 mL) on follow-up images compared to the patients without (resp. 20 ± 17 mL, p < 0.05; 13 ± 19 mL, p < 0.01; 29 ± 24 mL, p < 0.05). All IVIM penumbra perfusion lesions progressed to infarction despite thrombectomy treatment. Conclusions: IVIM is a promising tool to assess the quality of the collateral blood flow in hyperacute stroke. IVIM penumbra perfusion lesion may be a marker of nonsalvageable tissue despite treatment with thrombectomy, suggesting that the IVIM penumbra perfusion lesion might be counted to the stroke core, together with the DWI lesion.